The NAC transcription factor MdNAC29 negatively regulates drought tolerance in apple - Li, Sen; Jing, Xiuli; Tan, Qiuping; Wen, Binbin; Fu, Xiling; Li, Dongmei; Chen, Xiude; Xiao, Wei; Li, Ling (Frontiers in Plant Science, 2023)
Drought stress is an adverse stimulus that affects agricultural production worldwide. NAC transcription factors are involved in plant development and growth but also play different roles in the abiotic stress response. Here, we isolated the apple MdNAC29 gene and investigated its role in regulating drought tolerance. Subcellular localization experiments showed that MdNAC29 was localized to the nucleus and transcription was induced by the PEG treatment. Over-expression of MdNAC29 reduced drought tolerance in apple plants, calli, and tobacco, and exhibited higher relative conductivity, malondialdehyde (MDA) content, and lower chlorophyll content under drought stress. The transcriptomic analyses revealed that MdNAC29 reduced drought resistance by modulating the expression of photosynthesis and leaf senescence-related genes. The qRT-PCR results showed that overexpression of MdNAC29 repressed the expression of drought-resistance genes. Yeast one-hybrid and dual-luciferase assays demonstrated that MdNAC29 directly repressed MdDREB2A expression. Moreover, the yeast two-hybrid and bimolecular fluorescence complementation assays demonstrated that MdNAC29 interacted with the MdPP2-B10 (F-box protein), which responded to drought stress, and MdPP2-B10 enhanced the repressive effect of MdNAC29 on the transcriptional activity of the MdDREB2A. Taken together, our results indicate that MdNAC29 is a negative regulator of drought resistance, and provide a theoretical basis for further molecular mechanism research.